The Relationship between Sunnah and Local Culture: A Socio-Legal Analysis of Walimah Practices in Contemporary Muslim Communities - Anwar Habibi Siregar; Febri Amalia (QURU’: Journal of Family Law and Culture, 2026)
This study is grounded in the practice of walimah within Muslim societies, which is understood not only as a Prophetic tradition (sunnah) but also as a socio-cultural practice shaped by local customs. Normatively, walimah embodies values of gratitude, publicizing marriage, strengthening social ties, simplicity, and spiritual blessing. However, in practice, walimah has undergone a process of meaning expansion through the incorporation of customary elements, social status symbols, entertainment, and ceremonial elaboration, which may deviate from the Islamic principle of moderation. This study addresses the research questions of how the relationship between sunnah and local traditions is negotiated in the practice of walimah, and to what extent local culture can be accommodated within the framework of Islamic law without undermining its religious substance. This research employs a qualitative-descriptive approach with a socio-legal perspective. Data were collected through a comprehensive literature review of Islamic legal sources, including the Qur’an, Hadith, classical fiqh texts, and scholarly works on local cultural practices related to walimah. The analysis focuses on examining the interplay between normative Islamic legal principles as the ideal framework and lived social practices as empirical realities. The findings reveal that the relationship between sunnah and tradition in walimah is inherently negotiative. Local traditions can enrich the practice of walimah insofar as they do not contradict core Islamic principles such as permissibility (halal), moderation, public welfare (maslahah), and the prohibition of excess (israf). The study concludes that the ideal form of walimah is one that positions sunnah as the foundational value, while local culture serves as a contextual medium of social expression governed by Islamic ethical norms. The academic contribution of this research lies in strengthening socio-legal approaches within Islamic family law studies, particularly in understanding the dynamic interaction between religious norms and cultural practices in contemporary Muslim societies.